The Relationship of Clinicopathological Findings and PDGFR-β Expression With Tumor Recurrence in Gastrointestinal Stromal Tumors - Kaymaz, Esin; Taşdöven, İlhan and Barut, Figen (Turkish Journal of Gastroenterology, 2021)
Background: Considering the difficulty in predicting the biological behavior of gastrointestinal stromal tumors (GISTs) based on histological findings alone, genetic abnormalities have recently become an area of focus. Platelet-derived growth factor receptor (PDGFR), with 2 isoforms (α and β) is one of the mutations that play a role in the development of GIST. There are very little data determining the relationship of GIST with PDGFRβ which is associated with poor prognosis in other mesenchymal and epithelial tumors. In this study, we aimed to show the relationship between clinicopathological criteria and recurrence. We also wanted to evaluate the effect of PDGFRβ expression on recurrence and clinicopathological findings. Methods: We evaluated 40 GIST patients retrospectively for detailed clinicopathological findings, postoperative immunohistochemical tumor markers (CD117, Ki67), and also for tumor recurrence. Immunohistochemical examination for PDGFRβ was performed for the all GIST cases. Results: Tumor recurrence was related to male gender (P = .003), serosal localization (P = .004), surgical margins positivity (P = .001), risk group (P = .011), mitotic activity (P = .000), and Ki67 proliferation index (P = .000). PDGFRβ was not significantly associated with tumor recurrence (P = .277). Conclusion: We can say that the most important parameters related with recurrence of GISTs are mitotic activity and the Ki67 proliferation index. The determination of the cut-off value of the Ki67 proliferation index as 13% instead of 10% would be much more specific and sensitive. Although PDGFRβ may be used for the diagnosis of GIST as an alternative for PDGFRα in cases with cKIT negativity, it is not an indicator of tumor recurrence as in other tumors.